2015
DOI: 10.1016/j.ejpb.2014.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based technologies for retinal gene therapy

Abstract: For patients with hereditary retinal diseases, retinal gene therapy offers significant promise for the prevention of retinal degeneration. While adeno-associated virus (AAV)-based systems remain the most popular gene delivery method due to their high efficiency and successful clinical results, other delivery systems, such as non-viral nanoparticles (NPs) are being developed as additional therapeutic options. NP technologies come in several categories (e.g., polymer, liposomes, peptide compacted DNA), several o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 232 publications
0
60
0
Order By: Relevance
“…There are several types of NPs including metal-, lipid-, and polymer-based systems. They are different in size, charge, and structure but are all able to enter the cells, while avoiding the endosomes, and transfer the vector into the nucleus for gene expression (Adijanto and Naash, 2015). NPs allow combining several different plasmids in one particle to increase transgene expression (Klausner et al, 2010).…”
Section: Corneal Epithelial Wound Healingmentioning
confidence: 99%
“…There are several types of NPs including metal-, lipid-, and polymer-based systems. They are different in size, charge, and structure but are all able to enter the cells, while avoiding the endosomes, and transfer the vector into the nucleus for gene expression (Adijanto and Naash, 2015). NPs allow combining several different plasmids in one particle to increase transgene expression (Klausner et al, 2010).…”
Section: Corneal Epithelial Wound Healingmentioning
confidence: 99%
“…For example, polyethylene glycol-substituted polylysine (CK30PEG) NPs (further discussed below) have been used in several disease models (for review see (72)). These NPs are non-toxic, non-immunogenic and have no adverse effects on the retina after subretinal injection in wildtype mice or mice with retinal degeneration (73, 74), and importantly have a large carrying capacity (tested up to 14 kbp in the eye (75) and up to 20 kbp in the lung (76)).…”
Section: Therapeutic Approaches For Ocular Diseases With Gene Thermentioning
confidence: 99%
“…RP is associated with more than 100 mutations 12 in the different regions of the rhodopsin (Rho) gene that accounts for 30–40% of adRP 10 , and thus is genetically heterogeneous 3, 5, 10 . Rhodopsin protein helps to keep the structural integrity of the rod outer segments, as it was observed that Rho −/− mice were not able to extend rod outer segments.…”
Section: Ocular Disordersmentioning
confidence: 99%